Development of differential pulse voltammetric method for determining samarium (III) through electroanalytical study of the metal ion in acetonitrile using Box–Behnken design. Issue 4 (April 2021) - Wyantuti, Santhy; Pratomo, Uji; Manullang, Lastri A.; Hendrati, Diana; Hartati, Yeni Wahyuni; Bahti, Husein H.
Abstract: The development of methods for the efficient and reliable separation and routine analysis of rare-earth elements (REEs), including samarium (Sm), proceeds to draw in the interest of the many researchers, attributable to the similar physical and chemical properties of these elements. Note that although the voltammetric determination of Sm has been described in the literature, thus far, no chemometric and voltammetric methods for the quantification of the element in its mixtures with other lanthanides in an acetonitrile solution have been reported. This work was aimed toward the advancement of a method for the detection of Sm in acetonitrile, the intended function of which was to obtain a selective current response of Sm by Differential Pulse Voltammetry, utilizing the Box-Behnken experimental design, to identify the best conditions for the determination. In particular, the three selected factors for the experiment, namely the potential range, amplitude modulation, and the deposition time, were found to have optimal conditions of −1.5 to +1.0 V, 0.075 V, and 60 s, consecutively. The optimal conditions were observed to result in a selective current response for samarium with a detection limit of 2.25 mg/L and a limit of quantitation of 7.50 mg/L. Furthermore, the accuracy was 98.70% and the precision was found to be 1.91% in relative standard deviation (RSD), while the recovery was found to be 98.70%. Abstract : Samarium, Differential pulse voltammetry, Box–Behnken, Acetonitrile.